Zmiany w procesach zarządzania zasobami ludzkimi w kontekście procesów restrukturyzacyjnych przedsiębiorstw - Białowąs, Piotr (Human Resources Management: Changes in the Context of Restructuring Processes within Enterprises, 2008)
The author tried to present the main economy changes which are the sources of reengineering process in entities. These are the merger and acquisition process, tendency to raise value of a company. Among them the most popular is the procedure of management buyout in the last years. This procedure provides special consequences in human resources management. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 47-55